Evaluasi Keamanan Sistem Informasi Rumah Sakit: Metode Pengujian ISO 27001 di RS Khusus Mata Purwokerto - Akmal, Rafii Nur; Tarwoto; Deni Dwi Susilo; Rouf, Erik Halma; Kodir (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2025)
As service quality becomes paramount, ICT governance is increasingly important for organizations. This study will audit Purwokerto Eye Specialty Hospital's SIMRS against ISO/IEC 27001 standards to evaluate its information security posture. The implemented Hospital Management Information System (SIMRS) aims to support the integration of services and administrative processes, but faces various security challenges such as data loss and potential manipulation. The audit was conducted through observation, interviews, and analysis of existing security policies. The audit results show that information security incident management is in accordance with procedures, including handling, reporting, and corrective actions, with a fairly high level of security maturity. The study recommends periodic evaluation and security enhancements to ensure system resilience against future threats.